Three traditions of network research: what the public management research agenda can learn from other research communities - Berry, Frances S. et al. (2004)
This article identifies and describes the development of three parallel streams of literature about network theory and research: social network analysis, policy change and political science networks, and public management networks. Noting that these traditions have sometimes been inattentive to each other's work, the authors illustrate the similarities and differences in the underlying theoretical assumptions, types of research questions addressed, and research methods typically employed by the three traditions. The authors draw especially on the social network analysis (sociological) tradition to provide theoretical and research insights for those who focus primarily on public management networks. The article concludes with recommendations for advancing current scholarship on public management networks. - Reproduced.
Keywords: Public administration